If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying px + qx = 1 Solving px + qx = 1 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1qx' to each side of the equation. px + qx + -1qx = 1 + -1qx Combine like terms: qx + -1qx = 0 px + 0 = 1 + -1qx px = 1 + -1qx Divide each side by 'x'. p = x-1 + -1q Simplifying p = x-1 + -1q Reorder the terms: p = -1q + x-1
| (3-x)/(x-8)-(2x+4)/(8-x) | | 6+4s-5=8s+5-2s | | 81=27q | | 4x+4=-x+39 | | 2(x^2*2)=1 | | x+3.00=11.00 | | 5-2k=21+6k | | 3(x-2)=48 | | 10t=50 | | 35x^2+48x-27= | | n+3/8=7/10 | | 14x+4=16x-6 | | z/3+5=z/2+7 | | 1/8n+6=-5/8(n-16) | | n+3/58=7/10 | | n^2-2n+1=25 | | 30(20y-3)=194-y | | 2y/19y | | 21*10-6*10= | | 14x+14(3-2x)+7=4-x+5(2-3x) | | 14x=y-4 | | (3v-2)(3-v)=0 | | z/16=-28 | | z/12=-17 | | 4c-9=-5 | | -2/7x | | 2p+15p=34 | | x+3+1=15 | | 206+21x=-82x | | 180=0.5h(11+7) | | 5x+7=8x+-29 | | 10+x=44 |